Flexural reinforced concrete elements normal section bearing capacity evaluation in fracture stage. Issue 2 (3rd April 2017) - Slaitas, Justas; Hlavac, Zbynek; Šneideris, Arnoldas
Abstract: This article examines flexural reinforced concrete structures condition assessment process in existing buildings on the stage where the reinforcement stress is between the yield and the tensile strength. The research is made on V. Jokūbaitis proposed methodology directly measuring the compression zone height, allowing us to evaluate the behavior of reinforced concrete beam fracture sufficiently precisely. This paper confirms the hypothesis that, when reinforcement reaches yielding stress, elastic strain dominates in concrete's compression zone and it is reasonable to use triangular concrete compression zone diagram, without tensile concrete above crack evaluation. The methodology of reinforced concrete structures bearing capacity assessment according to limit normal section crack depth is proposed. There is established connection between bending moments, when reinforcement achieve yielding stress and tensile strength, which allows us to decide about structures bearing capacity reserve. The results are confirmed with experimental studies and calculated values obtained by methodologies based on different reduced stress diagrams of concrete's compressive zone.